Policework in a racist context: A qualitative study of retired African American police officers - Dockery-Sawyerr, Tangela C. (Journal of ethnicity in criminal justice, 2022)
The law enforcement community has faced great scrutiny in policing tactics and their interactions with marginalized communities and experiences of systemic racism. Moreover, increases in awareness have elicited alarms for reforming and defunding the police. To date, a plethora of literature exists in examining policing, systemic racism, and best practices for reform. However, few studies have explored the perspectives and experiences of racialized practices experienced by African American police officers. This qualitative study explored intradepartmental discrimination, police reform, and alternative policing practices. Findings demonstrate retired police officers’ perceptions of racial bias in policing, how these practices changed over time, and how they may influence decision-making in law enforcement.